Differences in Abdominal Body Composition According to Glycemic Status: An Inverse Probability Treatment Weighting Analysis - Han, Seungbong; Jeon, Young-Jee; Park, Gyung-Min; Lee, Tae Young; Park, Soon Eun; Yu, Gyeongseok; Kang, Byung Ju (Endocrinology and metabolism (Seoul), 2021)
Background: Several studies have reported that abdominal fat and muscle changes occur in diabetic patients. However, there are few studies about such changes among prediabetic patients. In this study, we evaluated the differences in abdominal fat and muscles based on abdominopelvic computed tomography in prediabetic and diabetic subjects compared to normal subjects.Methods: We performed a cross-sectional study using health examination data from March 2014 to June 2019 at Ulsan University Hospital and classified subjects into normal, prediabetic, and diabetic groups. We analyzed the body mass index corrected area of intra-abdominal components among the three groups using inverse probability treatment weighting (IPTW) analysis.Results: Overall, 8,030 subjects were enrolled; 5,137 (64.0%), 2,364 (29.4%), and 529 (6.6%) subjects were included in the normal, prediabetic, and diabetic groups, respectively. After IPTW adjustment of baseline characteristics, there were significant differences in log visceral adipose tissue index (VATI; 1.22±0.64 cm2/[kg/m2] vs. 1.30±0.63 cm2/[kg/m2] vs. 1.47±0.64 cm2/[kg/m2], P<0.001) and low-attenuation muscle index (LAMI; 1.02±0.36 cm2/[kg/m2] vs. 1.03±0.36 cm2/[kg/m2] vs. 1.09±0.36 cm2/[kg/m2], P<0.001) among the normal, prediabetic, and diabetic groups. Prediabetic subjects had higher log VATI (estimated coefficient= 0.082, P<0.001), and diabetic subjects had higher log VATI (estimated coefficient=0.248, P<0.001) and LAMI (estimated coefficient=0.078, P<0.001) compared to normal subjects.Conclusion: Considering that VATI and LAMI represented visceral fat and lipid-rich skeletal muscle volumes, respectively, visceral obesity was identified in both prediabetic and diabetic subjects compared to normal subjects in this study. However, intra-muscular fat infiltration was observed in diabetic subjects only.